Pengaruh Daya Tarik Produk Terhadap Konsumen Melalui Strategi Konten Instagram Ca Fiber di PT. Colar Creative Industri - Adam Avrilio Mustofa; Pungky Febi Arifianto (Pusat Riset dan Inovasi Nasional, 2023)
As time goes by, social media has an important role today, so it is widely used as a tool for sharing information and also as a marketing tool. As digital marketing continues to develop, one of the most widely used social media platforms is Instagram, which can become the main platform for products to market to consumers. This research aims to investigate the influence of product attractiveness on consumers through the implementation of content strategies on Instagram. The research method used is quantitative, collecting data through online surveys of Instagram users who have experience interacting with several products through the platform. The method used is a literature review of several studies.